Analysis of Physical Education Learning for Children with Special Needs in Inclusion Schools in Semarang City - Paramita, Emy Widya; Soenyoto, Tommy; Sumartiningsih, Sri (Journal of Physical Education and Sports, 2023)
This research aims to (1) Analyze the process of learning physical education activities in inclusive schools to improve the quality of life for children with special needs; (2) Examine the achievement of physical education learning in enhancing the quality of life for children with special needs in inclusive schools in Semarang city. The study employs a qualitative research design, with data sourced from Principals, Physical Education Teachers, and elementary school inclusion students in Semarang City. Data collection methods include observation, interviews, and documentation. The data gathered underwent a series of stages, including the initial collection, subsequent reduction, presentation, and formulation of conclusions. The findings highlight that students with special needs in inclusive schools generally exhibit mild disabilities. These children exhibit positive development in learning Physical Education, expressing happiness in engaging with the subject. Using the WHOQOL-BREF questionnaire, which consists of 26 questions assessing the quality-of-life index, Domain 1 (Physical) results show an average quality of life index deemed sufficient for 15 students. In Domain 2 (Psychological), most students demonstrate a good quality of life index. In Domain 3 (Social Relationships), most students display a good quality of life index. Lastly, in Domain 4 (Environment), results from the questionnaire of 15 students reveal a diverse quality of life, ranging from very good to excellent and sufficient. In conclusion, proficiency in physical education learning can positively impact the quality of life for inclusion students in Semarang City inclusion schools.